IN VITRO ANALYSIS OF THE EFFECTS OF FLUORIDE TOOTHPASTE WITH AND WITHOUT NATURAL HERBS ON Streptococcus mutans - santi chismirina (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2026)
Introduction: One way to prevent tooth decay is to brush your teeth twice daily for two minutes with fluoride toothpaste. Fluoride is an ingredient in toothpaste that can inhibit the growth of Streptococcus mutans. Currently, many fluoride toothpastes are combined with herbal ingredients for various purposes, such as whitening teeth and preventing discoloration. Aim: This study aimed to determine the effect of toothpaste containing fluoride with and without the addition of herbs in the form of xylitol, betel leaves, and siwak on S. mutans in vitro. Methods: The samples used were S. mutans ATCC 25175, which were exposed to three fluoride-containing toothpastes with added herbs (xylitol, betel leaf, and siwak, respectively) and one fluoride-containing toothpaste without herbs. Results: The results of the ANOVA test showed that there was a significant decrease in the number of S. mutans colony growth compared to fluoride toothpaste without the addition of herbs. The results of further tests showed that the average number of colonies of fluoride toothpaste and siwak was the least, namely 24.33 CFU/ml, followed by fluoride toothpaste with the addition of betel leaves, xylitol, and fluoride toothpaste without the addition of herbs, namely 31 CFU/ml, 32.67 CFU/ml, and 39 CFU/ml. Conclusion: Fluoride toothpaste with added herbs had a more significant effect in reducing the number of S. mutans colony compared to fluoride toothpaste without added herbs, with fluoride toothpaste with added siwak having the most significant effect on reducing colony growth compared to betel leaves and xylitol. Keywords: fluoride, Streptococcus mutans, siwak, xylitol, betel leaves